Implementasi High Order Fuzzy Time Series Multifactor pada Prediksi Harga Ayam Broiler di Pasar Malang - Fanny Aulia Dewi; Budi Darma Setiawan; Randy Cahya Wihandika (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Malang is the second largest population after Surabaya in East Java Province. Malang, which has increased its population every year, has resulted in the need for staples, especially broiler chicken meat, to increase. Broiler chicken meat is one of the sources of nutritious animal protein. Broiler chicken meat can be consumed by all levels of society so that there is an increase in demand every year. The availability of broiler chicken meat must always be fulfilled in the market and must pay attention to the price too. Broiler chicken meat prices on religious holidays (such as Eid al-Fitr, Eid Al-Adha, Christmas) there is a very striking increase compared to prices on normal days. The traders who need information about the price of broiler chickens every day in order to arrange sales so as not to miss. Therefore, a settlement is needed in forecasting the price of chicken using 72 data obtained from BPS in the period January 2013-December 2018. Based on the results of this study, the best MSE is 1,430 based on the highest number of orders.